2005
DOI: 10.1634/stemcells.2004-0153
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cell Factor Synergistically Enhances Thrombopoietin‐Induced STAT5 Signaling in Megakaryocyte Progenitors through JAK2 and Src Kinase

Abstract: Stem cell factor (SCF) has a potent synergistic effect during megakaryopoiesis when administered in combination with the major megakaryocytic cytokine, thrombopoietin (TPO). In this study we analyzed the underlying mechanisms with regard to STAT5 activity. TPO stimulation of MO7e cells resulted in STAT5 transactivation, which could be enhanced 1.6-fold by costimulation with SCF, whereas SCF alone did not induce STAT5 transcriptional activity. This costimulatory effect of SCF was reflected in an increase in TPO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 53 publications
1
14
0
Order By: Relevance
“…The analysis of downstream pathways commonly activated upon PDGFR activation showed that activation of the SRC family of kinases and the JAK2/STAT5 signaling pathways were both involved in RA-induced gonocyte differentiation (Manku et al 2014). Considering that STAT5 is a possible downstream target of SRC (Drayer et al 2005), it will be important to determine whether it is activated via JAK2, SRC, or another pathway in gonocytes. The presence of a variant PDGFRA form in gonocytes is interesting in view of the existence of a similar variant transcript identified in seminomas, the most common type of TGCTs (Palumbo et al 2002), and because of the possible relationship between improper gonocyte development and TGCT formation (Rajpert-De Meyts & Hoei-Hansen 2007).…”
Section: Transitional Gonocyte Differentiation In Rodentsmentioning
confidence: 99%
“…The analysis of downstream pathways commonly activated upon PDGFR activation showed that activation of the SRC family of kinases and the JAK2/STAT5 signaling pathways were both involved in RA-induced gonocyte differentiation (Manku et al 2014). Considering that STAT5 is a possible downstream target of SRC (Drayer et al 2005), it will be important to determine whether it is activated via JAK2, SRC, or another pathway in gonocytes. The presence of a variant PDGFRA form in gonocytes is interesting in view of the existence of a similar variant transcript identified in seminomas, the most common type of TGCTs (Palumbo et al 2002), and because of the possible relationship between improper gonocyte development and TGCT formation (Rajpert-De Meyts & Hoei-Hansen 2007).…”
Section: Transitional Gonocyte Differentiation In Rodentsmentioning
confidence: 99%
“…The ligand for KIT receptor is the stem cell factor (SCF) also known as KIT ligand, steel factor and mast cell growth factor. SCF is implicated in cell proliferation (Williams and Allan, 1996;Drayer et al, 2005), migration and survival (Bredin et al, 2003;Erlandsson et al, 2004). Recently, SCF has also been shown to be implicated in a resistance mechanism of malignant mesothelioma cells to drug treatment (Catalano et al, 2004).…”
mentioning
confidence: 99%
“…The increase in a number of platelets increased count may be due to the rise of several molecules such as SCF [4]. To determine the molecular mechanism of platelet production in mice model after treatment with guava extract, we evaluated the expression of SCF mRNA using qRT-PCR.…”
Section: Scf Expressionmentioning
confidence: 99%
“…Platelet generation is a two-stage process consisting of megakaryopoiesis and thrombopoiesis [4]. Megakaryopoiesis is a complex process that involves differentiation of hematopoietic stem cells (HSCs) to the megakaryocyte (MK), the proliferation of the progenitors, and MK maturation [18].…”
Section: Tpo Expressionmentioning
confidence: 99%
See 1 more Smart Citation